Analysis of the Mechanical Characteristics of Different Track Bed Types in Heavy-Haul Railway Tunnels. (24th May 2021) - Li, Ziqiang; Huang, Weiwei; Xu, Zhifan; Tang, Xiao; Wang, Mingnian; Yu, Li; Li, Zheng
Abstract : Based on field measurement data from the Fuyingzi Tunnel and Hongshila Tunnel on the Zhangtang Railway, a comparative analysis was conducted on the characteristics of a ballast bed and ballastless slab track, which are commonly used in the track structures of heavy-haul railway tunnels. According to the relevant domestic standards and the theory of the stress diffusion angle, a wheel-rail sharing ratio and theoretical calculation method for the added value of the trainload on the surface and bottom of different track bed types was proposed. In accordance with the measured data, the dynamic load thresholds and distributions on the surface and bottom of different track bed types were analysed and compared with the theoretical results. The results show that the theoretical equation has high accuracy and good applicability. The ballast bed can better cushion the heavy loads, while the ballastless slab track is better able to accomplish train load attenuation. In addition, the distribution on the bottom of the ballastless slab track is "triangular", while the distribution at the surface or bottom of the ballastless track and ballast bed is "saddle-shaped." The ballast bed is subjected to a greater load from the vehicle, and the long-term effect is more pronounced. These results can provide a theoretical basis for the stress analysis and design parameters of heavy-haul railway tunnel track beds.